How to set up a storytelling workshop in your classroom. (Journal of Parents and Teachers, 2025)
The article discusses how 5th-grade primary school students collaborated to develop a story based on the character Sonic. Due to the massive participation of all the students, the teacher found it quite challenging to choose which character would be published.
Keywords: characters; students; creativity; teachers